Preferensi Pakan dan Pengaruhnya Terhadap Pertumbuhan Kura-Kura Leher Ular Rote (Chelodina mccordi) di Kawasan Hutan Dengan Tujuan Khusus Oelsonbai Kelurahan Fatukoa Kecamatan Maulafa Kota Kupang - Patrisia Kristiani; Ludji Michael Riwu Kaho; Kayat Kayat (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2022)
This research was conducted to determine Feed Preferences and Their Influence on the Growth of the Rote Snake Neck Turtle (C. mccordi) in Oelsonbai Special Purpose Forest Areas, Fatukoa Sub-district, Maulafa District, Kupang City. This research was conducted from September to November 2021. Data collection on feed preferences and the effect of feed on growth used the observation method. Analysis of feed preference data used the Neu Index criteria calculation formula and growth data analysis used the growth and growth rate calculation formulas. The results showed that the type of feed that consumed the most was skipjack tuna. Through the calculation of feed preferences, the results obtained that the type of feed with the highest preference index was skipjack tuna, followed by tilapia, and the type of feed with the lowest level of preference was kombong fish. The results of the proximate analysis and literature study on the nutrients contained in the feed showed that the nutrients contained in tilapia, skipjack, and kombong needed C. mccordi for growth. Good food for growth and health of C. mccordi is shellfish. Skipjack tuna can be given as the main feed while tilapia and cockroach are given as additional feed. Feeding effect on the growth of C. mccordi. In general, the observation parameters experienced normal growth from the beginning to the end of the study week.